Unleashing potential: a data-driven exploration of identifying player potentialities through advanced analytics in sports - Bhowmik, Prashanta; Islam, Md. Khaliful; Khan, Nabil Shartaj; Acharjee, Ananna (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.